Economics on Railway Sleeper Supplies in Karimnager (East) DIVN. Andhra Pradesh - Murthy, A. V. R. G. Krishna (Indian Forester, 1967)
Forest types occuring Karimnager (East) Division, Andhra Pradeh described in detail with special reference to Eppa (Hardwickia binala) Forests and the local problems of economic working of Eppa timber. The need to work Eppa timber for Railway sleeper production was emphasised. The physical distribution of Eppa trees in various girth classes and that of sound logs converted for sleeper production is given with reference to the average per tree yield of economic Eppa wood fit for sleeper production. Comparative studies on hand and machine sawing per B.G. Unit are given. Work load of passing. Sleepers was indicated. Detailed yields from Eppa working Scheme in terms of sleepers sawn sizes and charcoal were given from field data collected. Economics of the Scheme are also Indicated for future reference.